Ocular Posterior Segment Involvement in Patients with Antiphospholipid Syndrome and Systemic Lupus Erythematosus - DİRESKENELİ, RAFİ HANER (TAYLOR & FRANCIS INC, 2020)
Purpose: To describe posterior segment findings of antiphospholipid syndrome (APS) and compare them with systemic lupus erythematosus (SLE).Methods: A total of 11 patients with primary APS, 29 secondary APS patients, and 29 SLE patients without APS were included. All patients were referred from rheumatology clinic for detailed ophthalmologic examination. When patients had suspicious lesions, fundus fluorescein angiography was performed (n = 56).Results: The most common retinal examination finding was peripheral venous tortuosity (17.5%) in APS, which was not observed in SLE group. Common FFA findings were pigment epithelial window defects (10%) and vascular filling delays (7.5%) in APS, which were observed in 27.5% and 3.5% of patients with SLE consecutively.Conclusion: Venous tortuosity was significantly more in patients with APS. There was no significant difference for other ocular findings between the groups. Ocular complication rate was lower compared to earlier reports, probably due to better management of disease activity with current treatment protocols.
Keywords: Antiphospholipid syndrome; drusen-like deposit; fundus fluorescein angiography; systemic lupus erythematosus; VASCULAR-DISEASE; MANIFESTATIONS; CHOROIDOPATHY; ANTIBODIES